A comparative prospective observational study of children and adults with immune thrombocytopenia: 2‐year follow‐up. Issue 6 (30th March 2018) - Schifferli, Alexandra; Holbro, Andreas; Chitlur, Meera; Coslovsky, Michael; Imbach, Paul; Donato, Hugo; Elalfy, Mohsen; Graciela, Elena; Grainger, John; Holzhauer, Susanne; Riccheri, Cecilia; Rodeghiero, Francesco; et al.
Abstract: Comparative clinical studies of children and adults with immune thrombocytopenia (ITP) are poorly covered in the literature. However, the accepted classification of ITP—childhood ITP and adult ITP—results in considerable differences in treatment protocols and practice guidelines. The analysis of the Pediatric and Adult Registry on Chronic ITP (PARC‐ITP) of patients at first presentation demonstrated fewer differences in clinical and laboratory findings at initial diagnosis between children and adults than expected. The present report of 2‐year follow‐up data supports the hypothesis that there are common aspects of childhood and adult ITP. Data of 3360 children and 420 adults were collected during the time of 2004 until 2015 at initial diagnosis. Follow‐up information was available for 51% and 33% of children and 66% and 49% of adults at 12‐ and 24‐months, respectively. Similarities were found in unexpected areas of ITP, such as the rate of late remission at 12 and 24 months, reported bleeding sites, platelet count in bleeders, and the frequency of treated patients with persistent or chronic ITP. Differences were confirmed for the overall rate of remission and treatment modalities. Unexpected differences were found in the percentage of nonbleeders, with more adults in the nonbleeder group. More studies are needed to investigate different age groups with the aim to optimize their management.